Epigenomic Indicators of Age in African Americans - Smith, Jennifer A (Hereditary Genet, 2014)
Age is a well-established risk factor for chronic diseases. However, the cellular and molecular changes associated with aging processes that are related to chronic disease initiation and progression are not well-understood. Thus, there is an increased need to identify new markers of cellular and molecular changes that occur during aging processes. In this study, we use genome-wide DNA methylation from 26,428 CpG sites in 13,877 genes to investigate the relationship between age and epigenetic variation in the peripheral blood cells of 972 African American adults from the Genetic Epidemiology Network of Arteriopathy (GENOA) study (mean age=66.3 years, range=39–95). Age was significantly associated with 7,601 (28.8%) CpG sites after Bonferroni correction for α=0.05 (p<1.89×10(−6)). Due to the extraordinarily strong associations between age and many of the CpG sites (>7,000 sites with p-values ranging from 10(−6) to 10(−43)), we investigated how well the DNA methylation markers predict age. We found that 2,095 (7.9%) CpG sites were significant predictors of age after Bonferroni correction. The top five principal components of the 2,095 age-associated CpG sites accounted for 69.3% of the variability in these CpG sites, and they explained 26.8% of the variation in age. The associations between methylation markers and adult age are so ubiquitous and strong that we hypothesize that DNA methylation patterns may be an important measure of cellular aging processes. Given the highly correlated nature of the age-associated epigenome (as evidenced by the principal components analysis), whole pathways may be regulated as a consequence of aging.